(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Mutrashmari- Urolithiasis is a common problem to mankind since the ancient times as one among the most troublesome obstructive uropathic disorders. Urolithiasis is a consequence of imbalance between stone promoters and inhibitors in the kidney i.e. it is a process which involves sequence of events in the formation of any urinary stone. Increased incidence of urolithiasis in this industrialized world is associated with improved standards of living and is strongly associated with race, ethnicity and region of residence. Approximately 2% percent of people experience the disease in lifetime, as it is more common in males than females. In ancient treatise, so many indigenous compounds are already mentioned in the treatment of Mutrashmari. In this study, the drug Veeratarvadi Kashaya, a unique drug mentioned in Ayurvedic classics was selected. The drug was given with twice amount of water to 30 patients for a period of 30 days. Follow-up were taken on 1st, 10th, 20th and 30th day. During this study, symptoms like burning/dribbling micturition, pain in abdomen and hematuria was the subjective criteria for all patients. Also size, site of calculus and hydronephrosis was the parameters seen via USG (abdomen & pelvis) during the study. After a month, patients got much relief from previous complaints and the USG was also normal than before. The action of Veeratarvadi Kashaya is due to its Mutrala (diuretic), Vikasi (anti-spasmodic), Ashmarighna (lithotripsic), Shothaghna (anti-inflammatory) properties which is helpful for painless disintegration and expulsion of calculus. It also helps in preventing the hyper-concentration of urine as well as further complications. In the present work, we have tried to study the action of Veeratarvadi kashaya, diet and lifestyle changes with respect to disintegration /expulsion of the calculi.